2015
DOI: 10.12816/0026018
|View full text |Cite
|
Sign up to set email alerts
|

Developing Shariah - Compliant Financial Services for the Muslim Customers in India

Abstract: India is an attractive and growing market for shariah-compliant financial services. Therefore, the purpose of this article is to propose a systematic process for developing new shariah-compliant financial services for the growing number of Muslim customers in the big emerging market of India. This article is based on a longitudinal case study of service innovation employed by a multinational bank providing a diverse range of financial services to the Indian Muslim customers. The findings suggest that a structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…While the literature has presented a strong case for the global adoption of Islamic finance, it has failed to answer the question, how to market and promote Islamic finance globally? (Alam 2015). Similarly, Azmat et al (2019) have emphasized the need for studies on how to persuade customers to adopt Islamic finance?…”
Section: Islamic Financial Service Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature has presented a strong case for the global adoption of Islamic finance, it has failed to answer the question, how to market and promote Islamic finance globally? (Alam 2015). Similarly, Azmat et al (2019) have emphasized the need for studies on how to persuade customers to adopt Islamic finance?…”
Section: Islamic Financial Service Sectormentioning
confidence: 99%
“…For example, our current review of the literature points to only limited coverage of the marketing issues in a limited number of countries. Some of the issues covered are product adoption (e.g., Islam and Rahman 2017;Richardson 2011), advertising and promotion (e.g., Schottmann 2014; Rammal and Zurbruegg 2007), service innovation (e.g., Alam 2015;Moktar et al 2006), consumer behavior (e.g., Kaakeh et al 2018;Korkut and Özgür 2017), and service quality analysis (e.g., Al-Jazzazi and Sultan 2014). With this in mind, several future research questions offer the substantial potential to extend our collective thinking about challenges in marketing of Islamic finance.…”
Section: Marketing Related Research Questionsmentioning
confidence: 99%
“…Likewise, the sources of inflation in India, both in the long run and in the short run were examined by using the co-integration method and found that in the long-run money supply (MS), depreciation of the rupee and supply bottlenecks causes inflation to rise in the country. It's revealed that in the long-run domestic factors such as monetary growth and supply bottlenecks dominate the external factors for a rise in the domestic prices in the economy [38] .…”
Section: Empirical Literaturementioning
confidence: 99%